Molecular characteristics of vancomycin-susceptible Staphylococcus aureus could help to predict treatment failure due to reduced vancomycin susceptibility - Adriana Medianeira Rossato; Keli Cristine Reiter; Renata Oliveira Soares; Thiago Galvão da Silva Paim; Gustavo Enck Sambrano; Pedro Alves d' Azevedo (Universidade de Santa Cruz do Sul, 2018)
Background and Objectives: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most frequent causes of healthcare-associated and community-acquired infections and with its advancement, vancomycin became the main therapeutic option. However, its indiscriminate 2 use favored the emergence of MRSA with reduced susceptibility to vancomycin, commonly associated with vancomycin treatment failure, persistent bacteremia, prolonged hospitalization and adverse clinical outcome. This study evaluated the occurrence of MRSA with reduced vancomycin susceptibility and determined some molecular characteristics in comparison with vancomycin-susceptible MRSA (VS-MRSA). Methods: Determination of antimicrobial susceptibility profile, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) for vancomycin, vancomycin-tolerance, SCCmec and agr typing were performed in a total of 177 MRSA. Thereafter, they were screened for hVISA by BHIA-3V and BHIA-6V and confirmed with population analysis profile - area under the curve method (PAPAUC). Results: VT-MRSA and hVISA phenotypes were found in 13.6% and 5.1% of clinical isolates of MRSA, respectively, and the presence of hVISA was statistically significant among VT-MRSA isolates (p